Spectrum of Medico-legal Deaths in Metropolis of Karachi: An Autopsy Based Study - Farhat Hussain Mirza; Qudsia Hassan; Romela Naz; Mahjabeen Khan (ziauddin University, 2024)
ABSTRACT Background: The number and variety of medico-legal deaths has inflated tremendously in the recent years in relation to acts of terrorism using explosive material and street crimes which often result in tragic death. Objectives: To determine the frequency, causes and manners of medico-legal autopsies at three major mortuaries in Karachi. Methods: A case study, involving the medico legal deaths autopsied at three major mortuaries in Abbasi Shaheed Hospital, Jinnah Postgraduate medical center and Civil Hospital, from March 01, 2008 to February 28, 2009. A detailed autopsy was conducted in each case to determine the cause of death. The bodies were first examined externally followed by dissection of body cavities in accordance with Robert Virchow's technique. The results were collected from the respective institutions on a structured performa and were statistically analyzed using SPSS version 15. The Mean ±SD was calculated for age. Results: Out of total 2,090 autopsies conducted during the period of study, 98.7% of the deaths were found to be due to unnatural causes. Homicides accounted for 54% of the deaths where as 39.3% were accidental deaths. Firearms were the most common cause of deaths (44.6%), followed by road traffic accidents (27.7%). Male to female ratio was 9:1 with 88.8% of the victims being males. Majority of the victims belonged to age group 19-32 years (47.3%). Conclusion: Homicides were the most common manner of death (54%), followed by accidents (39.3%). Frequency in relation to cause of death revealed firearm injuries accounting for 44.6% deaths followed by road traffic accidents (27.8%). KEY WORDS: Autopsies, Medico legal Deaths, Karachi, Homicides, Firearm Injury.